Answer:
-3 and -9
Step-by-step explanation:
First, it is helpful to write out what is given by the question, with variables x and y.
x*y = 27
x+y = -12
Now we will isolate a variable from one and plug it into the other:
y = -12 - x
x(-12-x) = 27
-x^2 -12x -27 = 0
x^2 + 12x + 27
(x + 9) (x + 3) = 0
x must be either -9 or -3
Now we plug those x-values into either equation to get their corresponding y-values:
-9 + y = -12
y = -3
-3 + y = -12
y = -9
We can see that the first x value (-9) corresponds to y = -3, and the second pair is -3 and -9. Either way, the pair is -3 and -9.
Therefore the pair of numbers must be -3 and -9.